Aspects of Esther: A Phenomenological Exploration of the Megillah of Esther and the Origins of Purim - Polish, Daniel F. (Journal for the study of the Old Testament, 1999)
Among the puzzles in the book of Ester is that of its origins. It is commonly agreed that its inclusion in the canon justified the Jewish community's appropriation of a holiday non-Jewish in origin. Many candidates have been suggested as the Ur-celebration upon which Purim is based. My effort employs a phenomenological, rather than historical or linguistic, analysis of various holidays to establish the identity of the proto-Purim. This article examines Esther's Haman/Mordecai doppelgänger figure and its correlation to the substitute king component of Sacae, the Babylonian New Year celebration. Other elements of the Purim celebration underscore this association with the New Year motif, leading us to identify Purim's origins with the Babylonian New Year festival.